Contractures with special reference in elderly: definition and risk factors – a systematic review with practical implications. (April 2014) - Offenbächer, M.; Sauer, S.; Rieß, J.; Müller, M.; Grill, E.; Daubner, A.; Randzio, O.; Kohls, N.; Herold-Majumdar, A.
Abstract Purpose: Contractures are common problems for the elderly with far reaching functional and medical consequences. The aim of this systematic literature review was to give an overview of contracture and to identify potential risk factors associated with contractures. Methods: A systematic literature search with two objectives limited to the last 10 years was performed to identify studies dealing with definition of contracture (objective 1 = O1) and with risk factors (objective 2 = O2). Predefined information including age, sample size, study design, setting, condition, joint, definition of contracture, mode of measurement, and whether inter- and/or intra-rater reliability were assessed, as well as risk factors of contracture were extracted. Results: One hundred and sixty one and 25 studies were retrieved. After applying exclusion criteria 47 studies (O1) and 3 studies (O2) remained. Only 9 studies (O1) provided a definition of contracture. In 3 studies (O2) several potential risk factors were identified. Conclusions: In most of the studies it seems that the presence of a contracture is equivalent with the presence of restriction in the range of motion (ROM) of a joint. Very little is known about risk factors for contractures. But it seems that immobility may play a pivotal role in the development of this condition. Implication for Rehabilitation The prevalence of contractures in nursing home residents is estimated at 55% with significant functional and medical consequences. In most studies, which were published in the last 10 years, the presence of a contracture is equivalent with the presence of restriction in the range of motion of a joint. Immobility seems to play a role in the development of contractures. Potential avenues to prevention of contractures and subsequent functional limitations are exercise programmes for and maintenance of mobility of the elderly.